Case Report: Upper limb superficial venous thrombosis associated with oral contraceptives mimicking soft tissue mass - Song, Jun Hyeong; Chun, Kyoung-Chul; Han, Gwan Hee; Yang, Seung-Woo; Yoon, Sang-Hee; Yuk, Jin-Sung; Ahn, Jaeki; Nam, Sang Hyun; Kim, Jongwoo; Kim, Myounghwan (Frontiers in Cardiovascular Medicine, 2023)
Background: Venous thrombosis associated with oral contraceptives (OCs) use occurs mostly at deep veins of lower extremity. Lesion of upper extremity is rare and the majority of thrombotic events occurring in the superficial vein of upper extremity are due to intravenous catheters. We present a rare case of superficial venous thrombus on upper extremity, in a young woman with a history of long-term oral contraceptive use.Case presentation: A 35-year-old woman with a history of 8-year-use of oral contraceptives, presented with a 2-year history of painfully palpable masses on her left forearm. The lesions mimicking soft tissue masses were confirmed to be superficial venous thrombus on ultrasound and magnetic resonance image. Conservative treatment including NSAIDs, vaso-protective agent, and aspirin was prescribed. Through consultation with department of obstetrics and gynecology, it was confirmed that the current oral contraceptives could be discontinued, and the pain was mostly improved after conservative treatment.If thrombotic events occur in the superficial vein of upper extremity without intravenous catheters, detailed medical history taking and the possibility of oral contraceptive (OCs) should be considered.